2019
DOI: 10.1177/0741932519855059
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Instructional Comparisons in Single-Case Research

Abstract: Comparison studies conducted to determine which instructional interventions are most efficient for teaching discrete behaviors to individuals with disabilities are potentially valuable, although some threats to internal validity may be more likely in these studies. Studies included in this review typically met common internal validity standards, such as reliability measurement, but often did not include controls specific to comparison designs. Comparisons often included young children with autism and were freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…There were larger differences between these conditions and the sample-first condition. Specifically, of the 13 comparisons where multiple conditions were efficacious, nine comparisons showed that the sample-first condition required at least 10% more sessions to reach mastery than the other conditions (Ledford et al, 2019; see Online Supporting Information for more details). This finding aligns with Vedora et al (2019) but does not replicate the efficiency advantage of the sample-first condition in Petursdottir and Aguilar (2016) and Schneider et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…There were larger differences between these conditions and the sample-first condition. Specifically, of the 13 comparisons where multiple conditions were efficacious, nine comparisons showed that the sample-first condition required at least 10% more sessions to reach mastery than the other conditions (Ledford et al, 2019; see Online Supporting Information for more details). This finding aligns with Vedora et al (2019) but does not replicate the efficiency advantage of the sample-first condition in Petursdottir and Aguilar (2016) and Schneider et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some intraverbal studies demonstrated quicker skill acquisition through picture prompts (e.g., Ingvarsson & Hollobaugh, 2011) while others supported the use of echoic prompt (e.g., Kodak et al, 2012). In the present study, we found active student response with picture prompt was more efficient in facilitating the acquisition of English‐to‐Chinese translations for five of the eight comparisons using the total sessions as the efficiency measure based on the criterion of 10% difference as proposed by Ledford et al (2019). However, when using total trials as the measure, all comparisons across participants produced differentiated results based on the same criterion.…”
Section: Discussionmentioning
confidence: 63%
“…Similar results were also obtained during her performance in Comparison 2 where she had a faster acquisition with the picture‐prompt condition (i.e., six sessions of 83 trials) than error correction with echoic prompt (i.e., eight sessions of 110 trials). As such, using Ledford et al's (2019) criterion of 10% difference, both comparisons for Lam yielded differentiated effects between the numbers of sessions and trials in two conditions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations